CircPIK3C2A Facilitates the Progression of Glioblastoma via Targeting miR-877-5p/FOXM1 Axis - Yang, Jian; Tian, Shuaiwei; Wang, Baocheng; Wang, Jiajia; Cao, Liangliang; Wang, Qinhua; Xie, Wanqun; Liang, Zhuangzhuang; Zhao, Heng; Zhao, Yang; Liao, Keman; Ma, Jie (Frontiers in Oncology, 2021)
Glioblastoma is a rare yet lethal type of tumor that poses a crucible for the medical profession, owing to its rapid proliferation and invasion resulting in poor prognosis. Circular RNAs (circRNAs) refer to a subclass of regulatory RNAs that are implicated in the regulation of cancerous progression. The current study aims to investigate the roles of circPIK3C2A in regulating proliferation and invasion of glioblastoma, and to clarify the molecular mechanism. qRT-PCR assays found that the expression level of circPIK3C2A was aberrantly higher in glioblastoma cell lines, in comparison with that in normal glia cells. The ectopic expression of circPIK3C2A acts to promote the proliferation, invasion and clonal formation of glioblastoma cells, while circPIK3C2A loss-of-function exerted exactly the opposite biological effects on the cells. The construction of subcutaneous xenograft tumor model in nude mice indicated that circPIK3C2A loss-of-function effectively diminished tumor load in vivo and prolonged the survival time of tumor-bearing animals. Luciferase reporter assay confirmed the interactive relationship among circPIK3C2A/ miR-877-5p and FOXM1. CircPIK3C2A function as competitive endogenous RNA via sponging miR-877-5p through certain binding sites, thereby modulating the expression of FOXM1. Our results collectively indicate that circPIK3C2A functions as ceRNA via mediating miR-877-5p/FOXM1 Axis, providing a novel perspective of applying CircPIK3C2A in the clinical intervention of glioblastoma in the future.